2023
DOI: 10.1186/s13071-023-05791-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a-3p prevents Schistosoma japonicum-induced liver fibrosis by targeting Roundabout homolog 1 in hepatic stellate cells

Abstract: Background Schistosomiasis is a serious but neglected parasitic disease in humans that may lead to liver fibrosis and death. Activated hepatic stellate cells (HSCs) are the principal effectors that promote the accumulation of extracellular matrix (ECM) proteins during hepatic fibrosis. Aberrant microRNA-29 expression is involved in the development of fibrotic diseases. However, less is known about the role of miR-29 in Schistosoma japonicum (S. japonicum)-induced hepatic fibrosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…39,40 Meanwhile, other studies have found that miR-29a-3p is involved in multiple organ fibrosis, including liver, lung, and renal interstitial fibrosis. [41][42][43] There are some binding sites among circPHF20L1, miR-29a-3p, and ROCK1 through miRDB (http://www.mirdb.org/). CircPHF20L1/ miR-29a-3p/ROCK1 may play a regulatory role in the development of myocardial fibrosis in DCM.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Meanwhile, other studies have found that miR-29a-3p is involved in multiple organ fibrosis, including liver, lung, and renal interstitial fibrosis. [41][42][43] There are some binding sites among circPHF20L1, miR-29a-3p, and ROCK1 through miRDB (http://www.mirdb.org/). CircPHF20L1/ miR-29a-3p/ROCK1 may play a regulatory role in the development of myocardial fibrosis in DCM.…”
Section: Discussionmentioning
confidence: 99%